Gene expression analysis in epileptic hippocampi reveals a promoter haplotype conferring reduced aldehyde dehydrogenase 5a1 expression and responsiveness. (15th December 2020) - Tsortouktzidis, Despina; Schulz, Herbert; Hamed, Motaz; Vatter, Hartmut; Surges, Rainer; Schoch, Susanne; Sander, Thomas; Becker, Albert J.; van Loo, Karen M. J.
Abstract: Increasing evidence indicates the pathogenetic relevance of regulatory genomic motifs for variability in the manifestation of brain disorders. In this context, cis ‐regulatory effects of single nucleotide polymorphisms (SNPs) on gene expression can contribute to changing transcript levels of excitability‐relevant molecules and episodic seizure manifestation in epilepsy. Biopsy specimens of patients undergoing epilepsy surgery for seizure relief provide unique insights into the impact of promoter SNPs on corresponding mRNA expression. Here, we have scrutinized whether two linked regulatory SNPs (rs2744575; 4779C > G and rs4646830; 4854C > G) located in the aldehyde dehydrogenase 5a1 (succinic semialdehyde dehydrogenase; ALDH5A1 ) gene promoter are associated with expression of corresponding mRNAs in epileptic hippocampi ( n = 43). The minor ALDH5A1 ‐GG haplotype associates with significantly lower ALDH5A1 transcript abundance. Complementary in vitro analyses in neural cell cultures confirm this difference and further reveal a significantly constricted range for the minor ALDH5A1 haplotype of promoter activity regulation through the key epileptogenesis transcription factor Egr1 (early growth response 1). The present data suggest systematic analyses in human hippocampal tissue as a useful approach to unravel the impact of epilepsy candidate SNPs on associated gene expression. Aberrant ALDH5A1 promoter regulation in functional terms can contribute to impaired γ‐aminobutyric acid homeostasis and thereby network excitability and seizure propensity.